Kebijakan moneter: Teori dan bukti empiris - Sardjonopermono, Iswardono (Economic Journal of Emerging Markets, 2016)
Monetary crisis accured in Indonesia has showed a serious weakness of monetary policy by Sentral Bank. As written in this paper, there are many weakness and mistakes of Sentral Bank as monetary policy maker in Indonesia.